Demystifying borderline personality disorder in primary care - Wu, Tina; Hu, Jennifer; Davydow, Dimitry; Huang, Heather; Spottswood, Margaret; Huang, Hsiang (Frontiers in Medicine, 2022)
Borderline personality disorder (BPD) is a common mental health diagnosis observed in the primary care population and is associated with a variety of psychological and physical symptoms. BPD is a challenging disorder to recognize due to the limitations of accurate diagnosis and identification in primary care settings. It is also difficult to treat due to its complexity (e.g., interpersonal difficulties and patterns of unsafe behaviors, perceived stigma) and healthcare professionals often feel overwhelmed when treating this population. The aim of this article is to describe the impact of BPD in primary care, review current state of knowledge, and provide practical, evidence-based treatment approaches for these patients within this setting. Due to the lack of evidence-based pharmacological treatments, emphasis is placed on describing the framework for treatment, identifying psychotherapeutic opportunities, and managing responses to difficult clinical scenarios. Furthermore, we discuss BPD treatment as it relates to populations of special interest, including individuals facing societal discrimination and adolescents. Through this review, we aim to highlight gaps in current knowledge around managing BPD in primary care and provide direction for future study.